Tensions within the sales ecosystem: a multi-level examination of the sales-marketing interface - Malshe, Avinash; Krush, Michael T. (Emerald Publishing Limited, 2020)
Purpose The purpose of this study is to understand one portion of the sales ecological system. This paper focuses on the mesolevel or intra-organizational system that includes the sales and marketing functions. This paper examines distinct tensions at three levels of the firm’s hierarchy and the mechanisms used to manage the tensions. Design/methodology/approach The authors use a qualitative data collection. A discovery-oriented process is used to understand the interconnections that exist among marketing-sales dyads at three organizational levels across several firms. Findings This paper uncovers distinct tensions and defenses exhibited by managers at each hierarchical level and this paper presents mechanisms that can are used to reduce the tensions. Research limitations/implications The multi-level perspective demonstrates the value of examining the intra-organizational aspect of the sales ecosystem. This paper uses a qualitative approach to highlight that sales-marketing tensions are unique to each of the hierarchical levels. This paper demonstrates that the tensions are a function of the unique roles each sales and marketing executive has within the organization. Practical implications To make the sales and marketing interface more effective, managers need to view tensions across the sales-marketing interface as complementary versus opposing forces. Managers must balance these tensions, rather than fight them and/or select one of the alternatives over the other. This paper suggests that paradoxical thinking may be a valued skillset for managers at each level of the organization. Originality/value The study uses a unique qualitative data set that examines the sales-marketing interface across three levels of an organizational hierarchy. Through this approach, this paper delineates specific tensions between marketing and sales within each level of the firm. This paper also describes mechanisms to manage the tensions common within the sales-marketing interface.
Keywords: Grounded Theory; Sales; Paradox; Ecological systems; Managing-sales interface